Avaliação farmacológica das aminas-traço β-feniletilamina e octopamina em canal deferente isolado de ratos - Silva, Karine Lima (2025)
Trace amines (TA) are found throughout the central nervous system at concentrations ranging from 0.1–100 ng/g tissue. Borowsky et al (2001) identified the superfamily of trace amine-associated receptors (TAAR), with several being expressed in specific regions of the central nervous system and peripheral tissues, including the male reproductive system. The mechanisms that regulate the contractile behavior of the vas deferens are of interest as targets for drugs designed to control ejaculation, with the possibility of TA playing important roles in molecular signaling pathways in this tissue. The aim of the present study was to evaluate and characterize the pharmacological effects of two trace amines, β-FEA and octopamine, on the contractility of the vas deferens and it signaling pathways. Muscle contractility experiments were recorded on a data acquisition system. RT-PCR was used to evaluate the gene expression of TAAR and adrenergic receptors and Western Blotting was used to evaluate the protein expression of TAAR. By constructing a concentration-effect curve on the basal tone of the isolated tissue, β-FEA and octopamine were able to generate concentration-dependent muscle contraction, also with changes in the frequency and amplitude of the phasic contractions generated and with a more pronounced response in the epididymal segment (EP) of the isolated vas deferens. In electric field stimulation (EFS) experiments, no significant tissue contractility responses were observed in the presence of β-FEA or octopamine. Through pre-contraction induced by phenylephrine (phe), a classic α-adrenergic agonist, it was observed that octopamine (> 100 µM) potentiated the contractile response generated by the agonist, an effect that was non-existent in the presence of β-FEA. In the presence of the adrenergic antagonist prazosin and phentolamine (phent), the AT contractile response was significantly reduced. As the response observed in the experiments with AT was excitatory, EPPTB (50 µM), a TAAR1 antagonist, was used indirectly in the presence of phent, however, no decrease in adrenergic blockade was observed in the presence of EPPTB. In the presence of pre-contractions induced by different concentrations of extracellular K+ (40, 60, 80 and 120 mM), both β-FEA and octopamine were able to potentiate the contractile response when the pre-contraction was generated by 40 mM K+, an effect also demonstrated for naphazoline (NFZ). In medium containing Ca2+, the contractile response of octopamine was blocked by nifedipine, a Ca2+ channel blocker. However, in the absence of Ca2+ and in medium containing Ba2+ the contractile response of octopamine was significantly reduced. It was observed that NFZ, an adrenergic agonist and potential TAAR4 agonist, similarly to AT, has a concentration-dependent contracting action that is more evident in the EP segment. Using molecular biology techniques, gene expression of TAAR1 and TAAR4 receptors was found to be smaller in the rat vas deferens than in the testis. However, the protein expression of these receptors in the vas deferens was comparable to the expression in the testis. β-FEA and octopamine produce a contractile effect in the isolated vas deferens of rats, with a more pronounced effect in the EP segment, which is probably related to the interaction with adrenergic receptors.